2013
DOI: 10.1007/s10464-013-9608-0
|View full text |Cite
|
Sign up to set email alerts
|

The (In)compatibility of Diversity and Sense of Community

Abstract: Community psychologists are interested in creating contexts that promote both respect for diversity and sense of community. However, recent theoretical and empirical work has uncovered a community-diversity dialectic wherein the contextual conditions that foster respect for diversity often run in opposition to those that foster sense of community. More specifically, within neighborhoods, residential integration provides opportunities for intergroup contact that are necessary to promote respect for diversity bu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
105
2
2

Year Published

2015
2015
2017
2017

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 94 publications
(127 citation statements)
references
References 39 publications
(43 reference statements)
6
105
2
2
Order By: Relevance
“…In the field today there is a ongoing discussion about this community-diversity dialectic; One side using agent-based simulation models to explore the dialectic argue that the contextual conditions that foster respect for diversity run in opposition to the ones that foster PSOC [61] [62] [63]. On the other side Brodsky [64] and Hill [65] state that there is no inherent dialectical relationship or conflict inherent to the concepts.…”
Section: Psoc and Diversitymentioning
confidence: 99%
“…In the field today there is a ongoing discussion about this community-diversity dialectic; One side using agent-based simulation models to explore the dialectic argue that the contextual conditions that foster respect for diversity run in opposition to the ones that foster PSOC [61] [62] [63]. On the other side Brodsky [64] and Hill [65] state that there is no inherent dialectical relationship or conflict inherent to the concepts.…”
Section: Psoc and Diversitymentioning
confidence: 99%
“…In spite of these different measures, this work largely arrives at the same conclusion: Diversity in neighborhoods appears to hamper the community connection for residents within. Alternatively, using agent-based simulations, Neal and Neal (2014) found that the increase of segregation may strengthen community connections. This begs the following question: Are individuals residing within segregated communities, marked by homogeneous racial/ethnic populations, really benefiting from a stronger sense of community connection as a product of living within these places?…”
Section: Introductionmentioning
confidence: 99%
“…This is noteworthy because the types of neighborly interactions that generate social capital seem to be rare among residents of different socioeconomic status in mixed-income NU projects (Chaskin & Joseph, 2011). While there is hope that social programming may mitigate this (Kleit, 2005), Cabrera and Najarian's (2013) and Neal and Neal's (2014) research dampen this as each finds social networks tend to flourish in contexts that are homogeneous. While there are other expected benefits of diversity, including access to resources and services, we focus on the implications for group interaction because of our interest in NU's relationship with processes of social exclusion and inclusion.…”
Section: Resultsmentioning
confidence: 99%